Pelatihan â€œTyping Masterâ€ Pada Siswa Smk BNM Plus Pariaman - Haslina, Welsi; Maretha Rissi, Dita; Hatta, Ermatati; Maryati, Ulfi; Mustika, Rasyidah (Akuntansi dan Manajemen, 2020)
The development of information and communication runs rapidly in the current modern era. So many technological discoveries in the field. Of course the impact is now making it easier for all the needs and desires of humans and will continue to grow every second. Formerly humans used typewriters to make letters, office administration, and other jobs related to typing. Over time and the development of technology, typewriters gradually replaced by the presence of a computer. The use of computers can help work in terms of making tasks both from the office and from school. So typing skills quickly and precisely are needed. Vocational school is a level of formal education that is ready to go into the world of work. The PKM activity was carried out at SMK Plus BNM Pariaman because this school only taught theories about typing 10 fingers without providing special training. So by giving theory alone, students are not accustomed to typing 10 fingers in accordance with adequate procedures. The goal of this activity is to increase the knowledge and skills of students to implement a 10-finger typing system and without looking at the keyboard. With this skill, the school will create graduates that are in line with industry needs.